Atlas Randstad Holland - Engel, Henk; Pane, Iskandar; van der Bogt, Olivier (OverHolland, 2018)
(1) Ijmuiden (2) Purmerend (3) Haarlem (4) Amsterdam (5) Naarden (6) Leiden (7) Alphen aan den Rijn (8) Mijdrecht (9) Hilversum (10) Den Haag (11) Zoetermeer (12) Gouda (13) Utrecht (14) Hoek van Holland (15) Vlaardingen (16) Rotterdam (17) Schoonhoven (18) Leerdam (19) Ouddorp (20) Hellevoetsluis (21) Oud Beijerland (22) Dordrecht (23) Gorinchem